Perbandingan Metode Moving Average dan Exponential Smoothing pada Peramalan Nilai Tukar Rupiah terhadap Dollar AS - Sayyidah Jasinda Amalia; Nunik Oktaviani; Garin Indra Prameswara; Yogo Dwi Prasetyo; M Yoka Fathoni (STMIK Budi Darma, 2022)
The currency exchange rate or known as the exchange rate is the price of one unit of foreign currency in the domestic currency or can be referred to as the currency exchange rate against current or future payments between the two currencies of each country or region. The exchange rate of a country's currency is strongly influenced by the flow of capital between countries. The Indonesian economy is heavily influenced by the international economy so that the Rupiah exchange rate is very much needed by the community in their economic life. Exchange rate data has very high volatility and tends not to be stationary. This study discusses the forecasting of the Rupiah exchange rate against the Dollar AS with two methods, namely Moving Averages and Exponential Smoothing. Accuracy analysis using Mean Absolute Deviation (MAD) and Mean Squared Error (MSE) methods. The software used in this research is the Quantitative Method (QM 5.3) software. The results of the study explain that the most appropriate forecasting method is used in analyzing the data. The Exponential Smoothing method forecasts the exchange rate of the Rupiah against the US Dollar with = 1.0 for January 1, 2022, which is Rp. 14,278 with MAD worth 29,105 and MSE worth 1564,619